Influence of post-synthetic graphene oxide (GO) functionalization on the selective CO2/CH4 adsorption behavior of MOF-200 at different temperatures; an experimental and adsorption isotherms study - Ullah, S. (Elsevier B.V., 2020)
In this work, a metal-organic framework (MOF-200) demonstrating microporosity was prepared from organic linker 1,3,5-tris(4-carboxy1,2-biphenyl-4-yl)-benzene) (H3BBC) and salt Zinc Nitrate Hexahydrate (Zn-(NO3)2Â·6H2O) via direct solution-based and catalyst-free method. The MOF-200 was further post-synthetically modified to MOF-200/GO with graphene oxide (GO). The structural and texture properties of MOF-200 and MOF-200/GO were investigated by FESEM, FTIR, Raman analysis, powder XRD, thermal stability, BET analysis, and selective adsorption behavior of CO2/CH4. The N2 adsorption-desorption isotherms reveal their highly microporous nature. The results showed the loss in surface area from 3624 m2/g (MOF-200) to 3359 m2/g (MOF-200/GO) due to post-synthetic modification with an improvement in CO2 uptake capacity of 15% due to successful surface functionalities attachment exhibiting remarkable CO2 philic nature. Both MOF-200 and MOF-200/GO were found crystalline in nature and highly stable under thermal conditions. Furthermore, the isotherms study by using the Langmuir isotherm, Freundlich isotherm, Sips isotherm, and Toth isotherm models was carried out. The isotherms-based results demonstrated favorable adsorption behavior with heterogenous systems and demand pore activation by employing high-pressure gas adsorption. Â© 2020